Augustine's political thought - Dougherty, Richard J. (Rochester studies in medieval political thought, 2019)
Introduction -- Politics, nature, and virtue -- St. Augustine and the problem of political ethics in the City of God / Richard J. Dougherty -- The other happy life : the political dimensions to St. Augustine's Cassiciacum dialogues / Michael P. Foley -- Peace in the order of nature : Augustine, Giles, and Dante / Peter Busch -- Deeds and words : latreia, justice, and mercy in Augustine's political thought / Ashleen Menchaca-Bagnulo -- The investigation of justice in Augustine's Confessions / Adam Thomas -- St. Augustine and ancient political philosophy -- The few, the many, and the universal way of salvation : Augustine's point of engagement with Platonic political thought / Thomas Harmon -- Echoes and adaptations in Augustine's Confessions of Plato's teaching on art and Politics in the Republic / Douglas Kries -- Truth, lies, deception, esotericism : the case of St. Augustine / Ryan Balot -- Augustine's ciceronian response to the ciceronian patriot / Veronica Roberts Ogle -- Augustine's City of God and Roman sacral politics / Daniel Strand -- Augustine and platonic political philosophy : the contribution of Joseph Ratzinger / Daniel E. Burns.